princess in love - Cabot, Meg; Meg Cabot (New York Harpercollins Publishers, Inc., 2002)
Princess mia may seem luckiest girl ever. But the truth is, mia spends all her time doing one of three things preparing for her nerve-racking entree into genovian society, slogging through the congestion unique to manhattan in december, and avoiding further smooches from her hapless boyfriend, kenny. For mia, being a princess in love is not the fairy tale it's supposed to be ... or is it?
english